Cytochrome P450 Omega-Hydroxylase 4a14 Attenuates Cholestatic Liver Fibrosis - Li, Sha; Wang, Chenghai; Zhang, Xiaxia; Su, Wen (Frontiers in Physiology, 2021)
Background: Cholestasis is a pathological condition involving obstruction of bile secretion and excretion that results in hepatotoxicity, inflammation, fibrosis, cirrhosis, and eventually liver failure. Common bile duct ligation (BDL) is a well-established murine model to mimic cholestatic liver fibrosis. We previously reported that cytochrome P450 omega-hydroxylase 4a14 (Cyp4a14) plays an important role in the pathogenesis of NAFLD related fibrosis. The goal of this study was to determine the role of Cyp4a14 in cholestatic induced liver fibrosis. Methods: C57BL/6 mice were subjected to BDL for 14 days, Cyp4a14 mRNA and protein levels were examined and compared with sham group. Cyp4a14 knockout mice and AAV-mediated overexpression of Cyp4a14 in C57BL/6 mice underwent BDL, liver histology and key fibrosis markers were examined. Results: Both hepatic Cyp4a14 mRNA and protein levels were markedly reduced in BDL liver compared with time-matched sham group. Cyp4a14 gene-deficient mice aggravates, whereas its overexpression alleviates BDL-induced hepatic fibrosis which were determined by liver function, liver histology and levels of key fibrotic markers including α-smooth muscle actin (α-SMA), transforming growth factor-β1 (TGF-β1), and collagen 1a2 (Col1a2). Conclusion: Cyp4a14 exerts a contrast role in different hepatic fibrosis model. Strategies that enhancing Cyp4a14 activity may be a potential strategy to cholestatic related liver fibrosis.